2014
DOI: 10.1142/s0218127414500898
|View full text |Cite
|
Sign up to set email alerts
|

Bifurcation of Critical Periods from a Quartic Isochronous Center

Abstract: This paper is focused on the bifurcation of critical periods from a quartic rigidly isochronous center under any small quartic homogeneous perturbations. By studying the number of zeros of the first several terms in the expansion of the period function in ε, it shows that under any small quartic homogeneous perturbations, up to orders 1 and 2 in ε, there are at most two critical periods bifurcating from the periodic orbits of the unperturbed system respectively, and the upper bound can be reached. Up to order … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…In this work, we extend the results presented in Peng and Feng by calculating the part of the averaging function of system that corresponds to the expression A . In order to do that, we perturb the center of system inside the whole class of quintic polynomial differential systems.…”
Section: Proof Of Theorem 11mentioning
confidence: 71%
See 2 more Smart Citations
“…In this work, we extend the results presented in Peng and Feng by calculating the part of the averaging function of system that corresponds to the expression A . In order to do that, we perturb the center of system inside the whole class of quintic polynomial differential systems.…”
Section: Proof Of Theorem 11mentioning
confidence: 71%
“…They showed that for | ε | ≠ 0 sufficiently small, systems can have at least eight limit cycles bifurcating from the periodic orbits of the period annulus of the uniform center located at the origin of system . Note that the authors improved the result of Peng and Feng by proving five additional limit cycles.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…In several papers as [3,10,25] it was shown that the limits cycles model many phenomena of the real world. After these works the non-existence, existence, the maximum number and other properties of the limit cycles have been extensively studied by mathematicians and physicists, and more recently, by biologists, economist and engineers, see for instance [4,17,18,19,26].…”
Section: Introduction and Statement Of The Main Resultsmentioning
confidence: 99%